2015
DOI: 10.1039/c5ce00147a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into solid and solution properties of quinizarin

Abstract: Polymorphism, crystal shape and solubility of 1,4-dihydroxyanthraquinone (quinizarin) have been investigated in acetic acid, acetone, acetonitrile, n-butanol and toluene. The solubility of FI and FII from 20 degrees C to 45 degrees C has been determined by a gravimetric method. By slow evaporation, pure FI was obtained from n-butanol and toluene, pure FII was obtained from acetone, while either a mixture of the two forms or pure FI was obtained from acetic acid and acetonitrile. Slurry conversion experiments h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The solubility of benzocaine was determined in pure organic solvents using a gravimetric method described previously. 11 Solutions with excess pure FI or FII were prepared in 30 mL glass vials, each containing a PTFE-coated magnetic stirrer and sealed with a screw cap with a PTFE coated insert. The vials were placed on a magnetic stirrer plate submersed in a water bath under agitation at 600 rpm, for at least 18 h at each temperature to allow equilibrium to be reached.…”
Section: Solubility Of Fi and Fiimentioning
confidence: 99%
“…The solubility of benzocaine was determined in pure organic solvents using a gravimetric method described previously. 11 Solutions with excess pure FI or FII were prepared in 30 mL glass vials, each containing a PTFE-coated magnetic stirrer and sealed with a screw cap with a PTFE coated insert. The vials were placed on a magnetic stirrer plate submersed in a water bath under agitation at 600 rpm, for at least 18 h at each temperature to allow equilibrium to be reached.…”
Section: Solubility Of Fi and Fiimentioning
confidence: 99%
“…DHXANT12); it seems likely that a transition relating them would require nucleation and growth. Careful experiments (Cheuk et al, 2015) showed that the Z 0 = 8 form is the more stable at room temperature. There are also high-Z 0 and low-Z 0 forms of 4,6-O-benzylidene--d-galactosyl azide, one with Z 0 = 6 (e.g.…”
Section: Kinetics Versus Thermodynamicsmentioning
confidence: 99%
“…Anthraquinone derivatives, which are extracted from the seeds of the Rubiaceae family of shrubs, include alizarin (1,2dihydroxyanthraquinone; C 14 H 8 O 4 ) and other polycyclic aromatic hydrocarbons. The colour of anthraquinone-based compounds can be modified by the type and position of the substituents attached to the anthraquinone nucleus (Nakagawa et al 2017;Cheuk et al, 2015;Tonin et al, 2017). Besides their application as pigments or dyes in textile, photographic, cosmetic and other industries (Wang et al, 2011), anthraquinone derivatives have been used for centuries for medical applications, for example, as laxatives (Oshio et al, 1985), antioxidants (Yen et al, 2000), antimicrobial (Xiang et al, 2008;Yadav et al, 2010) and anitiviral (Alves et al, 2004) agents.…”
Section: Chemical Contextmentioning
confidence: 99%